2023
DOI: 10.3390/cancers15061785
|View full text |Cite
|
Sign up to set email alerts
|

Use of Next Generation Sequencing to Define the Origin of Primary Myelofibrosis

Abstract: Primary myelofibrosis (PMF) is a chronic myeloproliferative neoplasm (MPN) characterized by progressive bone marrow sclerosis, extra-medullary hematopoiesis, and possible transformation to acute leukemia. In the last decade, the molecular pathogenesis of the disease has been largely uncovered. Particularly, genetic and genomic studies have provided evidence of deregulated oncogenes in PMF as well as in other MPNs. However, the mechanisms through which transformation to either the myeloid or lymphoid blastic ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(74 reference statements)
0
0
0
Order By: Relevance
“…However, some patients carried JAK2 mutation in both myeloid and lymphoid populations, indicating a neoplastic clone potentially originating from multipotent hematolymphoid stem cells [60]. This multipotent stem cell origin appeared to be more common in PMF [61]. Although animal models have demonstrated that driver mutations alone are sufficient to induce MPN [39,[62][63][64], JAK2 V617F has also been identified as an age-related mutation in clonal hematopoiesis of indeterminate potential (CHIP), without resulting in clonal proliferation.…”
Section: The Origin and Evolution Of Neoplastic Clonesmentioning
confidence: 99%
“…However, some patients carried JAK2 mutation in both myeloid and lymphoid populations, indicating a neoplastic clone potentially originating from multipotent hematolymphoid stem cells [60]. This multipotent stem cell origin appeared to be more common in PMF [61]. Although animal models have demonstrated that driver mutations alone are sufficient to induce MPN [39,[62][63][64], JAK2 V617F has also been identified as an age-related mutation in clonal hematopoiesis of indeterminate potential (CHIP), without resulting in clonal proliferation.…”
Section: The Origin and Evolution Of Neoplastic Clonesmentioning
confidence: 99%